Epigenetics of sepsis - Binnie, Alexandra (2020)
Recent evidence from the fields of microbiology and immunology, as well as a small number of human sepsis studies, suggest that epigenetic regulation may play a central role in the pathogenesis of sepsis. The term "epigenetics" refers to regulatory mechanisms that control gene expression but are not related to changes in DNA sequence. These include DNA methylation, histone modifications, and regulation of transcription via non-coding RNAs. Epigenetic modifications, occurring in response to external stressors, lead to changes in gene expression, and thus lie at the intersection between genetics and the environment. In this review, we examine data from in vitro studies, animal studies, and the existing human sepsis studies in epigenetics to demonstrate that epigenetic mechanisms are likely central to the pathogenesis of sepsis and that epigenetic therapies may have potential in the treatment of sepsis and its associated organ failures.